Coming to terms with democracy : Federalist intellectuals and the shaping of an American culture - Foletta, Marshall, 1955- (University Press of Virginia, 2001)
"In Coming to Terms with Democracy, Marshall Foletta contends that by callling for a new American literature in their journal, the second-generation Federalists helped American readers break free from imported neoclassical standards, thus paving the way for the American Renaissance."--Jacket